Enhancing Medication Adherence Among Patients With Schizophrenia and Schizoaffective Disorder: Mobile App Intervention Study - Khloud Al Dameery MSc, RN; Blessy Prabha Valsaraj PhD, RN; Mohammad Qutishat MSc, RN; Arwa Obeidat MSc, RN; Abdullah Alkhawaldeh PhD, RN; Sulaiman Al Sabei PhD, RN; Omar Al Omari PhD, RN; Mohammed ALBashtawy PhD, RN; Mohammad Al Qadire PhD, RN (SAGE Publishing, 2023)
Introduction Technology has permeated every aspect of our existence and the mental health sector is not exempt from this. Objectives The aim of this study was to test the impact of using a mobile phone app (MyTherapy pill reminder and medication tracker) on medication adherence in patients with schizophrenia and/or schizoaffective disorder. Methods Time series design was used. Fifty-one participants were recruited from tertiary hospitals in Oman. The Medication Adherence Rating Scale was used for assessing medication adherence. The data related to medication adherence were collected at baseline, 3 months later and 3 months after installing the program on participants' smartphones. SPSS data set used to analyze the data. Results A repeated-measures ANOVA found no significant change in the level of adherence among patients with schizophrenia and schizoaffective disorders at the start and 12 weeks later when the mobile app was installed ( p   =  .371). However, adherence scores improved significantly 12 weeks after installation of mobile app compared with the same group at the baseline and 12 weeks before the installation of mobile app ( p  < .001). Conclusion The mobile phone app was effective in improving the adherence level among patients. Installation of the program and teaching patients how to use it to improve their level of adherence is recommended.